Annotated translation of specific chapters of the book "Porqué fui Presidente" by Gustavo Noboa Bejarano. - Álvarez Henríquez, Desiré Estefanía (2017)
The following annotated translation was carried out with the purpose to let people to know more about the Ecuadorian political history. This piece of translation contains specific facts regarding one of the worst economic and political crisis of the country dated in 1999 – 2000 which included the holiday bank and the freezing of bank deposits followed by the dollarization. The book “Porqué Fui Presidente” narrates the circumstances in which the decisions of the country were taken and also by whom. It mentions the reaction of the Ecuadorian people and the participation of the Ecuadorian army in the overthrown of then President of Ecuador, Jamil Mahuad, and how the Vice President, Gustavo Noboa Bejarano, assumed the position as President of Ecuador. All the process led by the political instability is narrated from the point of view of the author, Gustavo Noboa, who includes details of his experience. The book which has only been presented in Spanish contains political and financial terminology Ecuador had during those years. The rendering of this book will represent an opportunity for other authors to let their work be recognized and contribute to their political culture.